Downregulation of Transcription Factor T-Bet as a Protective Strategy in Monosodium Urate-Induced Gouty Inflammation - Yang, Qi-Bin; He, Yong-Long; Zhang, Quan-Bo; Mi, Qing-Sheng; Zhou, Jing-Guo (Frontiers in Immunology, 2019)
Gout is sterile joint inflammation triggered by the damaging effects of monosodium urate (MSU) crystals accumulation. Previous studies suggest transcription factor T-bet plays an important role in inflammatory arthritis. Notably, mice lacking T-bet markedly reduced joint inflammation of rheumatoid arthritis models, however, the involvement of T-bet in gouty inflammation has yet to be clarified. Here, we took advantage of T-bet knockout (KO) mice to investigate the role of T-bet in the pathogenesis of MSU-induced gout inflammation. T-bet KO and wild type (WT) mice were used for models of acute inflammation induced with MSU crystals, including footpad, air pouch and peritonitis models. Inflammatory cytokines and phagocytosis were detected in bone-marrow-derived macrophages (BMDMs) from T-bet KO and WT mice treated with MSU crystals in vitro. In addition, T-bet expression in peripheral blood mononuclear cells (PBMCs) from gout patients was measured, as well as plasma inflammatory cytokines. We found that the levels of interleukin (IL)-17, IL-23 and interferon- were reduced, but tumor necrosis factor- was not, in BMDMs from T-bet KO compared with WT mice after MSU challenge in vitro, as well as MSU phagocytosis. In comparison with WT mice in vivo, the swelling index of T-bet KO mice was significantly decreased in the footpad model. T-bet deficiency also dramatically relieved MSU-induced inflammatory cell infiltration in peritonitis and air pouch models in vivo, and as well as the IL-1 levels of air pouch lavage fluid. In addition, plasma IL-17 and IL-23 levels were elevated in acute gout, whereas protein levels of T-bet were downregulated in PBMCs from acute gout patients and intercritical gout treated with MSU crystals in vitro as well. Transcription factor T-bet deficiency protects against MSU-induced gouty inflammation, suggesting that downregulation of T-bet could be a protective strategy and contribute to spontaneous remission of inflammation in acute gout.